2004
DOI: 10.1175/1520-0442(2004)017<3644:clstpa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Can Luzon Strait Transport Play a Role in Conveying the Impact of ENSO to the South China Sea?*

Abstract: The Luzon Strait transport (LST) from the Pacific into the South China Sea (SCS) is examined using results from a high-resolution ocean general circulation model. The LST from the model has a mean value of 2.4 Sv (Sv ϵ 10 6 m 3 s Ϫ1) and reaches its seasonal maximum (6.1 Sv westward) in winter and seasonal minimum (0.9 Sv eastward) in summer. Both the annual mean and seasonal variation of LST compare favorably with earlier observations. On an interannual time scale, LST tends to be higher during El Niño years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
263
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(279 citation statements)
references
References 30 publications
12
263
0
4
Order By: Relevance
“…Existing research has shown that, although the SCS has a climatological warm pool structure [78,79], its SST has significant interannual variation [80], and the interannual variability of the basin-wide SST is different in winter and summer [81]. Through the atmospheric and ocean circulations [82,83], the El Niño and Southern Oscillation (ENSO) signal can affect the oceanic variability in the SCS. The change of mixed layer depth (MLD) is also an important factor that impacts the SST [84], and in turn SST can impact the atmospheric circulation.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…Existing research has shown that, although the SCS has a climatological warm pool structure [78,79], its SST has significant interannual variation [80], and the interannual variability of the basin-wide SST is different in winter and summer [81]. Through the atmospheric and ocean circulations [82,83], the El Niño and Southern Oscillation (ENSO) signal can affect the oceanic variability in the SCS. The change of mixed layer depth (MLD) is also an important factor that impacts the SST [84], and in turn SST can impact the atmospheric circulation.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…Northward shift of the NECB during the El Nino years results in weaker Kuroshio Current in east of the Philippines. Subsequent reduction in the potential vorticity enables enhanced penetration of the Kuroshio water through the Luzon Strait Qu et al 2004). Conversely during the La Nina years, the southward shift of the NECB leads to a stronger Kuroshio Current and weaker LST and SCSTF.…”
Section: Implications Of the South China Sea Throughflowmentioning
confidence: 99%
“…The changes in ocean circulation and sea level associated with the monsoons are identified as the primary forcing mechanism of the SCSTF seasonal variability (Metzger and Hurlburt 1996). Meanwhile, its inter-annual as well as decadal variability are considered to be mainly governed by the ENSO Phenomenon (e.g., Qu et al 2004;Wang et al 2006b;Liu et al 2012). However, recent studies revealed that other large-scale phenomena such as the PDO also have a significant role in determining the low-frequency variability of the SCSTF (Yu and Qu 2013;Nan et al 2015).…”
mentioning
confidence: 99%
“…Well-equilibrated water enters through the NEC via the KI, with the main throughflow moving surface water south along the Vietnam coast during the NE monsoon and flowing out through the Java Sea and into the ITF. In the Makassar Strait, the seasonal mixing of surface waters is complex but reflects the relative contribution of source waters from (1) the Indonesian Throughflow (ITF) originating from NEC and South Equatorial Current (SEC) surface and subsurface water, and (2) the South China Sea Throughflow, that enters the SCS from the Luzon Strait and exits it through the straits to the south (Qu et al 2004(Qu et al , 2006. The relative contribution of these two source waters alternate during the SE and NW monsoon ( Gordon et al 2012).…”
Section: Post-bomb Period 1954 To 1986mentioning
confidence: 99%